Formulation of Pectin-Based Double Layer-Coated Tablets Containing Dexamethasone and Probiotics for Inflammatory Bowel Disease - Sagita, Erny; Winata, Ronaldo Ongki; Iswandana, Raditya (Pharmaceutical Sciences and Research, 2022)
Inflammatory Bowel Disease (IBD) is a chronic inflammatory condition in the colon that includes ulcerative colitis and Crohn’s disease. Dexamethasone is a steroid anti-inflammatory drug that can be used in IBD therapy. This study aims to obtain an optimum formulation of a dexamethasone drug delivery system for IBD treatment and to investigate its release profile based on an in vitro dissolution test. Dexamethasone was formulated as a double-coated tablet in combination with a probiotic L. acidophilus and B. longum mixture (1:1). The core tablets were produced using the wet granulation method, after which they were coated with pectin 4% b/v on the inner coat and a mixture of Eudragit L100 and S100 (1:4) on the outer coat. Three different core tablet formulas were prepared by varying the concentration of probiotics at 0%, 16% and 40% (F1, F2, and F3, respectively). The cumulative drug release of F1, F2 and F3 in HCl 0.1 N pH 1.2 for 2 hours were 42.92 ± 1.55%, 39.41 ± 4.10%, and 39.39 ± 1.63%, respectively, while in the phosphate buffer pH 6.8 they were 102.83 ± 1.56%, 105.08 ± 1.70%, and 98.81 ± 3.37% respectively, after 12 hours. From the results, we conclude that all formulas could be promising candidates for developing colon-targeted drug delivery.